Candida albicans Mastitis in Breastfeeding Woman: An Under Recognized Diagnosis - Merad, Yassine (Cureus, 2020)
Breastfeeding has been demonstrated to have many benefits for both mother and child. The diagnosis and management of Candida in the breastfeeding dyad are difficult because diagnosis is most often based on subjective signs and symptoms. Few studies have attempted to confirm the diagnosis with biological tests. A 26-year-old breastfeeding mother presented with stabbing breast pain, accompanied by erythematous, hyperkeratotic areola, and nipples. Histopathological results and direct mycological examination, followed by culture and auxanogram, revealed Candida albicans as an etiological agent of mastitis; the case was managed successfully by antifungal medication. Candida mastitis in lactating women is an under-recognized and under-treated cause of breast pain, hyperkeratosis over areola, and discharge of nipple should be assessed by biological tests. The hope is that with an increased awareness of this infection, more mothers will be appropriately treated and will thus be more likely to continue breastfeeding.